Printed Books of the 17th–18th centuries in the Collection of Literary Museum of A. Pushkin in Vilnius - Самодурова, Юлия Сергеевна Сергеевна (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English] The article contains a list of the 17th–18th centuries printed books in the French, German, Italian and Latin languages from the collection of Literary Museum of A. Pushkin in Vilnius. The article provides bibliographic data and short description of the books in brief. This article is one of the first attempts to introduce to researchers a list of rare old printed books of the Museum collection.